DEVELOPMENT AND OPTIMIZATION OF SOLID LIPID NANOPARTICLES OF ERLOTINIB USING DESIGN OF EXPERIMENTS: IN VITRO DRUGRELEASE AND IN VIVO PHARMACOKINETIC STUDIES - GANGULA, CHANDU VAMSHI; TOMAR, SEEMA; REDDYPAPAGATLA, POLI (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to develop and optimize erlotinib-loaded solid lipid nanoparticles (ERL-SLNs) using response surface methodology (RSM) with a box-behnken design. The goal was to enhance the drug's solubility, stability, and bioavailability by optimizing key formulation parameters and evaluating the in vitro and in vivo performance of the nanoparticles. Methods: ERL-SLNs were prepared using the hot homogenization method. Key formulation parameters, including the Quantity of Lipid, Concentration of Tween 80, and Homogenization Time, were optimized using RSM to achieve desirable characteristics such as Particle Size, Entrapment Efficiency, and Zeta Potential. The optimized ERL-SLNs were characterized for in vitro drug release using dissolution studies and fitted to various kinetic models. In vivo pharmacokinetic studies were conducted to evaluate the drug's bioavailability, maximum plasma concentration (Cmax), time to maximum concentration (Tmax), and half-life (t½) in comparison to conventional Erlotinib. Results: The optimized ERL-SLNs exhibited a Particle Size of 152.8 nm, Entrapment Efficiency of 87.6%, and Zeta Potential of-23.4 mV. The in vitro drug release study demonstrated a significant enhancement in the release profile of ERL-SLNs (85.4% in 24 h) compared to free Erlotinib (42.3% in 24 h). The release kinetics best fit the Korsmeyer-Peppas model (R² = 0.9942, n = 0.71), indicating a non-Fickian diffusion mechanism involving both drug diffusion and nanoparticle erosion. Pharmacokinetic analysis revealed a higher Cmax (1408.35 ng/ml) for ERL-SLNs compared to conventional Erlotinib (1185.81 ng/ml), along with a prolonged Tmax (6 h vs. 4 h) and extended t½ (6.88 h vs. 3.7 h). Conclusion: The study demonstrates that ERL-SLNs significantly improve the solubility, stability, and bioavailability of Erlotinib. The optimized formulation exhibited controlled drug release, enhanced pharmacokinetic properties, and prolonged therapeutic efficacy, highlighting its potential as an effective drug delivery system for Erlotinib.